1970
DOI: 10.1121/1.1912168
|View full text |Cite
|
Sign up to set email alerts
|

Pure-Tone Auditory Behavioral Thresholds in Three Species of Lemurs

Abstract: Absolute thresholds were determined for pure tones of frequencies 100 Hz-40 kHz by the method of constant stimuli using a two-bar operant technique. Lemurs of three subspecies were trained to press a white bar to turn on a tone lasting 5 sec. During the tone, a single press on a second (black) bar resulted in food reward. Failure to respond simply terminated the trial. Response in the absence of tone was scored as a false positive response and resulted in a «-sec shock of from 0.6 to 1.3 mA. Thresholds, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…It is interesting to evaluate our results in relation to the perceptual abilities of lemurs. Studies of the hearing abilities of Eulemur fulvus and E. macaco suggest that the perceptual sensibility of these two species is optimal at frequencies between 2000 and 15 000-20 000 Hz (Mitchell et al 1970), thus in the range of formants F2-F4 that we investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to evaluate our results in relation to the perceptual abilities of lemurs. Studies of the hearing abilities of Eulemur fulvus and E. macaco suggest that the perceptual sensibility of these two species is optimal at frequencies between 2000 and 15 000-20 000 Hz (Mitchell et al 1970), thus in the range of formants F2-F4 that we investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering only the free-field studies (speakerderived), researchers have employed numerous approaches such as averaging the intensity from numerous positions, using only the value from the most intense position (hot-spots), measuring from the approximate position of the center of the head, measuring from the approximate position of the pinna, and using models of the subjects with microphones placed at the ear position. Though the last approach might seem intuitively to be the most precise because it incorporates sound field disturbances caused by the subject itself, only 2 laboratories have used it (Bennett et al 1983;Mitchell 1970;Mitchell et al 1970Mitchell et al , 1971. A potential problem with the hot-spot approach is that it assumes that the subject will sample a sound from the most intense area; hence sampling away from the area will produce threshold estimates that are too high.…”
Section: Lonsbury-martin and Martin 1981mentioning
confidence: 97%
“…Taken at face value, there appear to be few reasons to reject the audiogram for Eulemur macaca produced in the study by Mitchell et al (1970). They employed a fairly standard conditioning procedure and psychophysical techniques and used an extended range speaker to deliver the test tones.…”
Section: Malagasy Lemurs: Lemuroidsmentioning
confidence: 97%
See 1 more Smart Citation
“…One view receiving considerable support (Bragg and Dreher, 1969;Clack and Herman, 1963;Mitchell, Gillette, Vernon, and Herman, 1970;Mitchell, Vernon, and Herman, 1971) was advanced by Harris (1943). Harris pared the effectiveness of his aversive control technique with an appetitive procedure used by Wendt (1934) and concluded that aversive stimuli provide a more efficient means of conditioning behavior and collecting reliable data.…”
mentioning
confidence: 99%